Case report: First case of early adenoid cystic carcinoma and squamous cell carcinoma collision cancer treated by endoscopic submucosal dissection - Liang, Zheng; Wei, Yongqiu; Li, Peng; Xu, Rui; Zhou, Qiaozhi; Zhang, Shutian (Frontiers in Oncology, 2023)
Background: Collision cancer, a rare tumor, rarely occurs in the esophagus. Most reported cases of esophageal collision cancers are advanced cancers that can only be treated with surgery or palliative chemoradiotherapy. Here, we report a rare case of collisional squamous cell carcinoma (SqCC) and adenoid cystic carcinoma (AdCC) that was detected in the early stages by endoscopy. Case summary: A 66-year-old man presented with retrosternal pain after swallowing and underwent endoscopy. Pathological biopsy showed high-grade squamous intraepithelial neoplasia. The lesion was removed by endoscopic submucosal dissection (ESD) after magnification and endoscopic ultrasonography. Postoperative pathology proved that the lesion was collision cancer comprising SqCC and AdCC. After six months of postoperative follow-up, there was no recurrence of esophageal cancer. Conclusions: We provided a case report related to the diagnosis and treatment of esophageal collision cancer, especially early collision cancer. More research is needed to provide insights into the management of collision cancers.